Early psychological intervention following the 2014 Nepal snowstorm. Issue 1 (December 2016) - Oz, Idit; Tatsa-Laur, Lucian; Kreiss, Yitshak; Fructer, Eyal; Itzhak, Avraham; Sarid, Orly
Abstract The following is a case study of the blizzard of October 2014, an Israeli rescue team, the Special Mental Health Team (SMHT) of the Israeli Defense Forces Medical Corps, was sent to the disaster area to rescue Israeli trekkers. The SMHT intervention was provided immediately following the traumatic events with the purpose of lowering stress-related symptoms, shortening recovery time and reducing post-traumatic stress disorder symptoms that could occur in the future. Forty Israeli trekkers were assessed by SMHT: 75 % (n = 30) had mild acute stress reaction (ASR) symptoms and 25 % (n = 10) had severe acute stress disorder (ASD) symptoms. All participating trekkers receiving the intervention as a way to alleviate symptoms reported no symptoms of ASR and ASD following the intervention. Trekkers with mild ASR reported full recovery after 1 week and trekkers with ASD reported full recovery after 3 months. This case study describes the psychological intervention conducted by SMHT for the surviving trekkers following the blizzard and aims to extend the knowledge base of mental health intervention at the early phases of disaster. A research study should be conducted to develop a measurement tool capable of evaluating the effect of a short-term intervention conducted in the field.